2017
DOI: 10.1007/s00213-017-4619-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of serotonin in personality inference: tryptophan depletion impairs the identification of neuroticism in the face

Abstract: Serotonergic mechanisms mediate the expression of personality traits (such as impulsivity, aggression and anxiety) that are linked to vulnerability to psychological illnesses, and modulate the identification of emotional expressions in the face as well as learning about broader classes of appetitive and aversive signals. Faces with neutral expressions signal a variety of socially relevant information, such that inferences about the big five personality traits, including Neuroticism, Extraversion and Agreeablen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The facial expressions, different image acquisition angles, different lighting conditions, and face coverings (glasses, masks, etc.) will all bring great differences to the same face [ 8 ]. Therefore, improving the recognition accuracy of the face recognition system under complex conditions is a problem we need to study and improve.…”
Section: Introductionmentioning
confidence: 99%
“…The facial expressions, different image acquisition angles, different lighting conditions, and face coverings (glasses, masks, etc.) will all bring great differences to the same face [ 8 ]. Therefore, improving the recognition accuracy of the face recognition system under complex conditions is a problem we need to study and improve.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on investigating the relationship between common genetic polymorphisms and specific psychological characteristics for distinct candidate genes, with some studies showing that the neurotransmitters 5-hydroxytryptamine (5-HT) (serotonin), 5-hydroxytryptophan (5-HTP), and dopamine play an important role in personality traits [ 11 , 12 ]. Psychological characteristics have been mainly studied in association with the serotonergic system because neurotransmission mediated by 5-HT contribute to several psychological functions, such as emotional instability, anxiety, and depression [ 13 ]. Previously published studies have also shown that low levels of platelet 5-HT, and 5-HT metabolites, are associated with forms of impulsive or psychopathic behavior [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the compositions of the amino acid mixtures are distinct [58,59]. And, the gender difference is taken into account, i.e., the amino acid quantities of both ATD and placebo balanced beverages differ between males and females [47]. Moreover, inconsistencies exist regarding the effects of ATD on personality traits and disorders, attributing to the health state and characteristics of the subjects.…”
Section: Tph2 1176 Estonian Subjects Rs4570625mentioning
confidence: 99%